Fewer Charges are being Laid in the Health Practitioners Disciplinary Tribunal: Should we be Concerned? - Davies, Kim (Victoria University of Wellington Law Review, 2015)
Since the Cartwright Report was produced 27 years ago, it has become accepted that the needs of patients should be at the centre of our health system – including when things go wrong. This article examines professional disciplinary charges laid against doctors in the Health Practitioners Disciplinary Tribunal, and compares them with those laid in its predecessor organisation, the Medical Practitioners Disciplinary Tribunal. It concludes that fewer charges, particularly charges that relate to clinical misconduct, are coming before the Tribunal, and discusses the implications of this change. The article questions whether this evolving practice could undermine some of the purposes of the Tribunal and lead to a less patient-focused system.